Why us, Mr. President?: the U.S. boxing team and the boycott of the 1980 Moscow Olympic Games - Webster, Walter C. (Kansas State University, 2018)
This thesis highlights the consequences of the 1980 US boycott of the Olympic Games in Moscow from the perspective of the Olympic boxers. Beginning with a review of scholarly work on the Olympics and their surrounding politics, I outline how the White House, under President Jimmy Carter, manipulated the United States Olympic Committee (USOC) into supporting a boycott. I conclude that the political actions of the Carter Administration affected an entire nation's participation in an Olympic event. Exploring the socio-political circumstances surrounding the 1980 US Olympic boycott, my study seeks to answer three questions: First, what political tactics did the Carter Administration use to implement a boycott designed to pressure Russia to withdraw troops from Afghanistan? Manipulation of the USOC and threats to cut funding pushed compliance with Carter's agenda. As a result, the Carter administration’s actions included using US boxer Muhammad Ali as a pawn in an effort to persuade athletes to support a boycott. Few athletes felt comfortable speaking out against such high-level political strategies. Historically, the US denounced any nation's attempt to use the Olympic Games to make a political statement; this was exemplified in the US’s decision to send black and Jewish athletes to the 1936 Olympic Games in Berlin, despite the obvious dangers these athletes faced in the midst of the Nazi regime. As noted in the German press, allowing “wooly-haired niggers with protruding lips” to compete with Aryans was a disgrace. Second, what was the real reason Carter sought a boycott? The Carter Administration saw participation in the Moscow Games as “…signify[ing] an attitude of indifference toward the continuing occupation of Afghanistan by Soviet troops.” One possible explanation of the boycott, then, was to raise awareness about human rights atrocities within the Soviet Union and beyond during the Moscow Games. Perhaps the boycott was Carter’s desperate last effort to revive his presidential reputation after several instances of critical failure as President of the United States, including the Iranian-US hostage outrage (1979), the failed US hostage rescue attempt (1980), and economic inflation so extreme it contributed to a dramatic downward spiral in Carter’s re-election poll numbers. Third, what was the real impact of the 1980 Olympic boycott? How did athletes and coaches become victims of the IOC (International Olympic Committee) and the US government? For many of the prospective medalists, a boycott permanently slammed shut the only open window of opportunity and robbed them of potential fame and financial gain. My work shows that the 1980 boycott not only strained international relations, but also significantly altered the lives of the athletes, coaches, and teams beyond the 1980 Olympics.
Keywords: Jackie Beard; Richie Sandoval; Rayford Collins; Olympic boycott; Carter administrationOlympic games